Straightforward Route to Superhydrophilic Poly(2-oxazoline)s via Acylation of Well-Defined Polyethylenimine - Sedlacek, Ondrej; Janouskova, Olga; Verbraeken, Bart; Hoogenboom, Richard (Biomacromolecules, 2019)
Herein, we describe a new method for the synthesis of superhydrophilic poly(2-alkyl-2-oxazoline)s (PAOx) from poly(2-ethyl-2-oxazoline) (PEtOx). A well-defined linear polyethylenimine was prepared from PEtOx by controlled acidic hydrolysis of its side-chains followed by reacylation with different carboxylic acids. Using this protocol, we obtained a series of new hydrophilic PAOx containing side-chain ether groups with potential in biomaterials science. The relative hydrophilicity of the polymers was assessed, revealing that poly(2-methoxymethyl-2-oxazoline) (PMeOMeOx) is the most hydrophilic PAOx reported to date. Additionally, the amorphous poly(2-methoxy-ethoxy-ethoxymethyl-2-oxazoline) (PDEGOx) shows the lowest reported glass transition temperature (-25 °C) within the PAOx family to date. The biomedical potential of the prepared polymers was further fortified by an in vitro cytotoxicity study, where all polymers appeared to be noncytotoxic. The described synthetic protocol is universal and can be extremely versatile, especially for PAOx that are difficult to prepare by conventional cationic ring-opening polymerization due to the monomer interference and/or degradation.
Keywords: Oxazoles; Vitrification; Transition Temperature; oxazoly; Humans; HeLa buňky; tranzitní teplota; lidé; HeLa Cells; vitrifikace; polyethylenimin; Polyethyleneimine; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions